Effect of Celestite Precipitation in Compacted Illite on the Diffusion of HTO, 36Cl-, and 22Na+. (December 2017) - Fukatsu, Yuta; Van Loon, Luc R.; Shafizadeh, Amir; Grolimund, Daniel; Ikeda, Yasuhisa; Tsukahara, Takehiko
Abstract: From viewpoints of long-term safety assessments of disposal systems, it has become an important issue to clarify effects of porosity in compacted illite on diffusion behavior of non-sorbed species, cations, and anions. Therefore, in this study, celestite precipitation was artificially induced in pellets of compacted illite, and the amount and position of the precipitates were measured by neutron radiographic analysis. Neutron images showed selective clogging in the pores of the compacted illite. Moreover, a tracer-diffusion experiment using a solution containing tritiated water (HTO), cationic 22 Na +, and anionic 36 Cl - was performed. I was found that HTO and 22 Na + passed through the compacted illite which had been subjected to precipitation, while diffusion of 36 Cl - did not occur. This fact indicates that HTO and 22 Na + were able to diffuse, but anion exclusion of 36 Cl - occurred. The effective diffusion coefficient values of HTO and 22 Na + in compacted illite subjected to precipitation were much lower than for illite not subjected to precipitation. These results signify that the diffusion behavior of water, cation, and anion in small-sized pores of compacted illite is restricted by celestite precipitation, and is strongly influenced by the porosity and the arrangement of the illite particles.